1964
DOI: 10.2466/pms.1964.19.3.743
|View full text |Cite
|
Sign up to set email alerts
|

Learning of Redundant Material Presented through Two Sensory Modalities

Abstract: Ss were given a series of learning trials with stimulus materials of differing degrees of meaningfulness and redundancy using three modes of presentation. All Ss received one list of the stimulus materials through an auditory presentation, one list visually and one list audio-visually. Forty-eight Ss learned lists of nonsense syllables, 48 learned lists of common words, and 48 learned lists of words with constraint. One-fourth of each group received the stimuli at the rate of one each 4 sec., one-fourth at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

1969
1969
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 8 publications
1
9
1
Order By: Relevance
“…This conclusion is supported by both basic and applied research studies that have repeatedly demonstrated that information presented aurally persists longer in short-term memory and is less vulnerable to interference than visually presented information. It is worth mentioning that these findings conflict with the empirical evidence interpreted in support of the information processing and communication theories discussed in the second section of this report (e.g., Hsia, 1977;Paivio, 1978;Van Mondfrans & Travers, 1964).…”
Section: Discussioncontrasting
confidence: 99%
“…This conclusion is supported by both basic and applied research studies that have repeatedly demonstrated that information presented aurally persists longer in short-term memory and is less vulnerable to interference than visually presented information. It is worth mentioning that these findings conflict with the empirical evidence interpreted in support of the information processing and communication theories discussed in the second section of this report (e.g., Hsia, 1977;Paivio, 1978;Van Mondfrans & Travers, 1964).…”
Section: Discussioncontrasting
confidence: 99%
“…Text was superior to sound when the verbal information was a list of words (Severin, 1967), instructions (Sewell & Moore, 1980), four-line poems (Menne & Menne, 1972), and nonsense syllables (Chan, Travers, & Van Mondfrans, 1965;Van Mondfrans & Travers, 1964). However, one study (Van Mondfrans & Travers, 1964) found no learning differences between auditory and textual words. Also, if the learner's visual channel is already occupied, then it may be more appropriate to use audio verbal information than textual information.…”
Section: Characteristics Of the Materialsmentioning
confidence: 93%
“…Several studies (Menne & Menne, 1972;Severin, 1967;Van Mondfrans & Travers, 1964) found that text-only conditions produced better learning than audio-only conditions. However, unlike audio conditions, text conditions also allow the learner to process the verbal information at his or her own pace.…”
Section: Use Elaborative Mediamentioning
confidence: 96%
“…While clustering studies have not yet addressed themselves to this issue, recall studies present conflicting evidence. Van Mondfrans & Travers (1964) found no signiflCant differential recall performance under visual and audi~visual modes, and asserted that combined sensory modes merely provided redundant stimulus input. More recently, however, studies by both Murray (1965) and Wong & Bleving (1966) have found that recall scores increase as the number of modalities in which stimulus cues are presented is increased (the additivity-of-cues hypothesis).…”
mentioning
confidence: 99%